Identity Graph of Finite Cyclic Groups - Maria Vianney Any Herawati; Priscila Septinina Henryanti; Ricky Aditya (Universitas Sanata Dharma, 2021)
This paper discusses how to express a finite group as a graph, specifically about the identity graph of a cyclic group. The term chosen for the graph is an identity graph, because it is the identity element of the group that holds the key in forming the identity graph. Through the identity graph, it can be seen which elements are inverse of themselves and other properties of the group. We will look for the characteristics of identity graph of the finite cyclic group, for both cases of odd and even order.